Healing and the atonement - Petts, David (1993)
The purpose of the thesis is to examine the doctrine that physical healing is provided in the atonement. This is defined as "the view that Christians may claim healing from sickness on the grounds that Christ has already carried that sickness for them just as he has carried their sins". The theological and literary origins of the doctrine are traced and developments and modifications noted, particular reference being made to the Classical Pentecostal groups among which the doctrine is largely to be found. The New Testament passages used to support the doctrine are identified. These include Matthew 8:17, 1 Peter 2:24, Galatians 3:13, 1 Corinthians 11:29-30, James 5:14-15, and Mark 16:15-18. The conclusion is drawn that none of these passages supports the doctrine as it was originally propounded. The doctrine is also examined in the light of a possible relationship between healing and salvation, healing and the Gospel, sickness and sin, sickness and Satan, and sickness and suffering. The bearing on the doctrine of New Testament references to sick Christians and to the art of medicine is also considered. The examination of these themes leads to a conclusion that a modified form of the doctrine might well find a basis in the New Testament. Theological difficulties dealt with include the problem of relating the word "atonement" to sickness and the notion that Bible verses are "promises" to be "claimed". Practical and pastoral difficulties are also considered. In the final chapter a modification to the doctrine is proposed. Healing may be understood to be in the atonement both ultimately and indirectly. This is based on the Pauline teaching that those in Christ are to be clothed with an incorruptible body at the Parousia. Meanwhile healings occur as a work of the Spirit who is given to Christians as an αρραβών of their inheritance.